New insights on interpretation methodologies for analyzing complex onshore tectonic settings of Colombian sedimentary basins - Chavez Ballesteros, L.; Nimmagadda, Dr Shastri; Rincón Pabon, C.; Cardona Mora, P.; Chernikoff, A. (2012)
By virtue of their geography, onshore Colombian sedimentary basins are tectonically active in Latin America. These basins have undergone several phases of rifting at different geological periods with different extensional and compressional geological events. Deformation of structures and existence of fractures within clastics and carbonates, even including unconventional shales, silts, clay- and mudstone associated reservoirs, is not uncommon within both Tertiary and Cretaceous sequences. These productive basins are favorably located in the southwestern extension of Maracaibo basin of Venezuela, but falling within Colombian territory, where commercial quantities of hydrocarbons produced within multiple zones (from fractured reservoirs) for several decades. For this purpose, a systematic seismic sequence mapping approach has been followed up with a total of 13 seismic sequences and para-sequences, integrating different 2D and 3D seismic vintages with hundreds of drilled-well data. In order to understand the structural complexity, a rigor is made on interpretation of structure, isochrones, isopach, conventional and special post-stack attribute maps for all seismic sequences. Fault mapping is done at individual sequences for understanding the fracture systems, all along NS-EW trending fault systems. Based on integrated interpretation of structure and attribute maps of interpreted horizons, leads and prospects are identified including their risk assessment. Special focus is on data integration and interpretative integrated workflows, which has reduced the risk and ambiguity in interpretation, including insight of structural complexity and improved understanding of fractured structures and reservoirs.